1867 Mich. Pub. Acts 2d Reg. Sess. 68, No. 266, § 31, pt. 12. - (:unkn) unknown (General Publisher, 1867)
To regulate the buying, selling, and using of gunpowder, fire-crackers and fire-works, and other combustible materials, to regulate and prohibit the exhibition of fire-works, and the discharge of fire-crackers and fire-arms, and to restrain the making or lighting of fires in the streets and other open spaces in said village.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER; DISCHARGE